Modification on Spectral Conjugate Gradient Method for Unconstrained Optimization - Abbas Yakubu, Usman; Mamat, Mustafa; Afendee Mohamed, Mohamad; ., Sukono; Rivaie, Mohd (International Journal of Engineering and Technology, 2018)
The classical Newton’s direction and spectral conjugate gradient direction are the prominent directions in solving large-scale unconstrained optimization problems. Using the standard secant equation, a modified spectral CG method (MSCG) is proposed, the scheme is a modification of Birgin and Martinez spectral CG method (SCG). Sufficient descent property as well as global convergence has been proved by strong Wolfe line search. Numerical outcome shows that the method is practically effective when compared with classical PRP, FR and spectral CG methods.